2020
DOI: 10.1007/s11013-020-09669-3
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Approach of End-of-Life Care, Social Rites, and Bereavement Outcomes: A Transnational Perspective

Abstract: The current article focused on examining the potential benefits of the End-of-Life (EoL) informal caregiving, communication, and ritualistic behaviors in adaptation to the conjugal bereavement across two different cultural-background contexts: France and Togo, West Africa. The investigation adopted a transnational approach including a total of 235 bereaved spouses. Despite the variation in the length of time since death, no significant difference was found between the Togolese and French bereaved with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In French bereaved individuals, experiencing more intimate communication with the dying spouse was associated with a higher level of postloss growth. The authors concluded that informal caregiving to the dying, communication with the dying, and ritual support need to be promoted as integrated components of end-of-life care (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In French bereaved individuals, experiencing more intimate communication with the dying spouse was associated with a higher level of postloss growth. The authors concluded that informal caregiving to the dying, communication with the dying, and ritual support need to be promoted as integrated components of end-of-life care (7).…”
Section: Discussionmentioning
confidence: 99%
“…Rituals around grief and death have been practiced since the early beginnings of culture (3)(4)(5). Across countries, communities and historical periods, rituals have been a crucial element in dealing with grief and loss (6)(7)(8)(9). Although many traditionally religious practices have been decreasing in Western societies, grief rituals remain in secular contexts (9).…”
Section: Introductionmentioning
confidence: 99%
“…The present study represents an international contribution to the validation of the TGI‐SR+ in French‐speaking countries. Prior published French studies relied on translated versions of the Inventory of Traumatic Grief‐30 items (Delespaux et al, 2013; Delespaux & Zech, 2015; Zech, 2006), the Inventory of Complicated Grief‐Revised (ICG‐R) (Gana & K'Delant, 2011; Kokou‐Kpolou et al, 2017; Kokou‐Kpolou, Moukouta, Sani, et al, 2020) and short version drawn from ICG‐R items (Kokou‐Kpolou, Moukouta, Sani, et al, 2020, Kokou‐Kpolou et al, 2021). Thus, there is a lack of formal and reliable validated ICD‐11 and DSM‐5‐TR PGD assessment tools in French‐speaking countries.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many valid resources for helping understand established grief responses, it is vital to recognize the uniqueness of each individual's grief experience. Kokou-Kpolou et al (2020) found variations in the amount of self-reported post-loss growth and intensity of grief reaction between different groups and in some instances even within a specific group of bereaved individuals, providing evidence of the uniqueness of each person's grief journey. Listening attentively with one's heart and offering the gift of presence conveys respect of the individual and where he/she is in the grief journey.…”
Section: Traveling Considerations: Responses To Griefmentioning
confidence: 87%